Integrasi Statistical Process Control dan Failure Mode And Effect Analysis Guna Meminimalisasi Defect Pada Proses Produksi Pipa PVC - Ananda Hernawan; Nina Aini Mahbubah (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
Quality can be referred as fitness to use. Furthermore, Quality standard is considered as a way in order to meet customers’ need.  PT AZ is a manufacture enterprise which produce polyvinyl chloride (PVC) pipes. This firm has been implementing a Standard Operating Procedure (SOP) in maintaining defect with no more than 2,5% reject product during process production. However, such defects have been happened in production line which were not meet company standards. This study aims to evaluate defect along production process in order to find suitable solution in improving product quality. Seven Tools and Failure and Mode and Effect Analysis (FMEA) were used as research method.  The results showed that there were 3 types of defects, namely spot defect, sink marks ant scratch defect. Furthermore, the results of the Cause-and-effect diagram show that human error, materials and machine are considered as main factors in contributing such defect. In addition, result from FMEA analysis detect that analysis and calculation of the highest RPN 147, namely the human factor is considered as the highest Risk Priority Number with 147 score. This study suggest that further training and supervision should be give to employees in order to improve employers’’ knowledge